The theatre of Yes - Pallares-Elias, Marina (Amfiteater (Ljubljana), 2021)
Tejidos is a community artistic project that aims to develop a community to give voice to the particular stories of those who live in Oaxaca (women and the deaf community) and Mexico City (older adults). The project has been funded by the Arts Council England (2018) and Iberescena (2019). "Theatre of Yes" is a methodology that uses the power of beauty as a language to break the stereotypes of situations that society views with apathy. By creating a provocative and emotional performance, we can transform the lives of people who suffer social exclusion. Yet, how can we create a high-quality performance with people who are not professional actors but have stories that should be shared? How can we use powerful performances as an axis of change? How can emotions be the motor for the struggle against the social oppression that many groups suffer? Artistic work has helped us to observe how creativity pushes people to find a freer self and, above all, to be close to the essence of the human being. The base of the Theatre of YES brings together the universal characteristics, honesty, simplicity, humility and generosity. The characteristics of the methodology developed with these groups are the yes as a weapon against the non-worthy self, beauty as the axis of change, physical theatre according to the Lecoq methodology.
Keywords: beauty; družbena preobrazba; gledališče da-ja; Greek Choir; grški zbor; kvaliteta napredovanja; lepota; quality as excellence; social transformation; Theatre of Yes